Basis of Learning in Urban Communities: Cultural-Historical Activity Theory (CHAT) and the Limits of Contemporary Adult Learning Theories - Junghwan Kim; Intak Kwon (Adult Education Research Conference, 2011)
The purpose of this paper is to examine CHAT as an alternative approach to understanding learning in urban communities as a means to overcome the challenges of existing adult learning theories. The authors argue that CHAT provides a comprehensive theoretical view to understand learning in urban communities driven from activities within socio-cultural contexts.
Keywords: Learning in urban community; CHAT